FORMULASI DAN UJI SIFAT FISIK SEDIAAN KRIM DENGAN VARIASI KONSENTRASI EKSTRAK ETANOL DAUN KELAPA SAWIT (Elaeis guineensis Jack) - Idawati, Idawati; Patimah, Raudatul; Ahdyani, Risa (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Elaeis guineensis Jack. leaves contain flavonoid compounds which act as antioxidants to protect the body from bad influences that can cause skin damage by free radicals. One of the technological developments to treat that can be assisted by cream preparations. Cream has various advantages, namely that it is easy to spread evenly, easy to clean or wash, practical and works on local tissue, not sticky, especially in o/w creams. The aim of this research was to determine the effect of variations in the concentration of palm oil leaf ethanol extract on the physical properties and antioxidant potential of oil palm leaf ethanol extract cream. Oil palm leaves were extracted using the maceration method using 96% ethanol solvent to produce a thick extract. Palm oil leaf ethanol extract is made in cream dosage form with varying concentrations of palm oil leaf ethanol extract, FI (0.5%), FII (1%), and FIII (1.5%). The cream preparations were tested for physical properties including organoleptic tests, homogeneity, pH, viscosity, stickiness and spreadability. Based on the test results, all cream formulas meet the test requirements for homogeneity, pH, viscosity, adhesion and spreadability according to the requirements for cream preparations for use on the skin.